A fast Monte Carlo cell-by-cell simulation for radiobiological effects in targeted radionuclide therapy using pre-calculated single-particle track standard DNA damage data - Lim, A.; Andriotty, M.; Yusufaly, T.; Agasthya, G.; Lee, B.; Wang, C. (Frontiers in Nuclear Medicine, 2023)
We develop a new method that drastically speeds up radiobiological Monte Carlo radiation-trackstructure (MC-RTS) calculations on a cell-by-cell basis. The method is based on random sampling and superposition of single-particle-track (SPT) standard DNA damage (SDD) files from a "precalculated" data library, constructed using the RTS code TOPAS-nBio, with "time stamps" manually added to incorporate dose-rate effects. This time-stamped SDD file can then be input into MEDRAS, a mechanistic kinetic model that calculates various radiation-induced biological endpoints, including DNA double strand breaks (DSBs), misrepairs and chromosomal aberrations, and cell death. As a benchmark validation of the approach, we calculate the predicted energy-dependent DSB yield and the ratio of direct-to-total DNA damage, both of which agree with published in-vitro experimental data. We subsequently apply the method to perform superfast cell-by-cell simulation of an experimental in-vitro system consisting of neuroendocrine tumor cells uniformly incubated with 177 Lu. The results for residual DSBs, both at 24 and 48 hours post-irradiation, agree well with the published literature values. Our work serves as a proof-of-concept demonstration of the feasibility of cost-effective 'in silico clonogenic cell survival assay' for the computational design and development of radiopharmaceuticals, and novel radiotherapy treatments more generally.